The influence of product innovation and brand image on samsung smartphone purchase decision at bandung city - Didi Tarmidi; Ayunda Tri Mulyani (Enrichment : Journal of Management, 2023)
The buying decision for consumers is the result of various considerations in deciding to buy a product from various options that include the purchase of smartphone on the various choices available. There is a tendency because the majority of consumers to choose the brand from product innovation, price, service, and brand image for researchers try to reveal the magnitude of the influence product innovation and brand image about the purchasing decision of Samsung Smartphone brand at Bandung city. The method used is quantitative data analysis with multiple linear regression. The results of research from 100 samples taken provided information that product innovation and brand image had a significant influence on purchasing decisions by 49,5%. The variable that must be prioritized to get more significant influence is product innovation. Meanwhile, the product innovation variable is partially proven to have a greater constant than the brand image variable.